Pedagogical transformation of equitable education through 5.0 competencies in elementary schools - Herma Susanah; Yusuf T. Herlambang (Curricula: Journal of Curriculum Development, 2025)
In the 21st century, pedagogic transformation requires an educational approach oriented toward justice and critical thinking, particularly in preparing elementary students to respond to global challenges. This study aims to examine the application of 5.0 skills, including critical thinking, creativity, collaboration, communication, and care in learning based on social justice principles. Using a qualitative literature review, data were collected from various contemporary sources, including scientific journals, reference books, and relevant research findings, for the period 2015-2023. The study's findings reveal that a critical pedagogic model that integrates 5.0 skills has been effective in increasing student involvement, strengthening social awareness, and fostering mastery of essential competencies in the 21st Century. Further analysis shows that successful implementation requires a more flexible curriculum reorganization accompanied by an ongoing teacher professional development program. This research concludes that this approach is not only relevant to contemporary needs but also plays a strategic role in achieving inclusive and equitable education. Implicitly, systematic policies are needed to encourage the adoption of this model in the basic education system.    Abstrak Di era Abad 21, transformasi pedagogik mengharuskan pendekatan pendidikan yang berorientasi pada keadilan dan berpikir kritis, khususnya dalam menyiapkan murid tingkat dasar untuk menjawab tantangan global. Studi ini bertujuan mengkaji penerapan kemampuan 5.0 meliputi berpikir kritis, kreativitas, kolaborasi, komunikasi, dan kepedulian dalam pembelajaran yang berprinsip keadilan sosial. Dengan menggunakan metode studi literatur kualitatif, data dikumpulkan dari berbagai sumber terkini seperti jurnal ilmiah, buku referensi, dan hasil penelitian relevan periode 2015-2023. Temuan penelitian mengungkap bahwa model pedagogik kritis yang mengintegrasikan kemampuan 5.0 terbukti efektif dalam meningkatkan keterlibatan murid, penguatan kesadaran sosial, serta penguasaan kompetensi esensial Abad 21. Analisis lebih lanjut menunjukkan bahwa keberhasilan implementasi memerlukan penyusunan ulang kurikulum yang lebih fleksibel disertai dengan program pengembangan profesional guru secara berkelanjutan. Penelitian ini menyimpulkan bahwa pendekatan tersebut tidak hanya relevan dengan kebutuhan zaman tetapi juga berperan strategis dalam mewujudkan pendidikan yang inklusif dan berkeadilan. Implikasinya, diperlukan kebijakan sistematis untuk mendorong adopsi model ini dalam sistem pendidikan dasar. Kata Kunci: keadilan sosial; kemampuan 5.0; pendidikan kritis; transformasi pedagogik